Parent- and teacher-reported long-term effects of parent training on child conduct problems in families with child protection and other support services: a randomized controlled trial - Piia Karjalainen; Päivi Santalahti; Eeva T. Aronen; Olli Kiviruusu (BMC, 2021)
Abstract Background This randomized controlled trial (RCT) evaluated the long-term effectiveness of the Incredible Years® (IY) Parenting Program in modifying children's externalizing problems among families in Child Protection Services (CPS) and using other special support services. We also examined whether parent-reported effects of the IY® generalize to the daycare/school setting as reported by teachers. Methods Participants in the study were 3-7-year-old children with behavioural problems (N = 102 at baseline, N = 89 at one-year follow-up). Participants were randomized to intervention (N = 50) and control groups (N = 52) after the baseline assessment. The intervention group received 19-week IY® Parenting Program. The effectiveness of the intervention was analyzed using linear mixed model. Results Our previously reported pre-post intervention effects on CBCL (Child Behavior Checklist) and ECBI (Eyberg Child Behavior Inventory) were not sustained to the one-year follow-up. Child conduct problems decreased from baseline to follow-up in both intervention and control groups. The positive changes were not observed at daycare/school from baseline to post-intervention or to the one-year follow-up, and there were no significant differences in changes between the groups. Conclusions Evidence-based parenting program IY® seems to be an effective intervention for child conduct problems in the short term in families in the CPS context, but sustaining the positive effects and generalizing them to the daycare/school context are challenging. Trial registration: The trial is registered in the ClinicalTrials.gov registry (NCT03239990), Registered August 4th, 2017; https://clinicaltrials.gov/ct2/results?cond=&term=NCT03239990&cntry=&state=&city=&dist=